A study of various surgical approaches for the treatment of mandibular condylar fractures - Shanmugasundaram; Gnanam; R Sathish; Ajay Mohan (Wolters Kluwer Medknow Publications, 2012)
Introduction: Condylar fractures are one of the commonest fractures account for 25-35% of all mandibular fractures. In our study we analyzed the advantages, disadvantages ,ease of exposure and complications in various surgical approaches for open reduction and internal fixation of displaced mandibular condyle fracture with miniplates fixation. Aims & objectives: The aim of our study was to analyze the various surgical approaches used for open reduction and internal fixation of mandibular condyle fracture. Materials & method: We selected a total of 7 patients with condylar fractures in which 4 males and 3 females selected randomly. Age of these patients ranged from 21-27years. 3 patients had left condyle fracture associated with right parasymphysis, 2 were isolated condylar fractures and 2 bilateral condyle fractures. Results: A total number of 7 patients were taken for our study purpose and the results were analyzed based on the ease and access to the mandibular condyle with various approach and its surgical complications. Conclusion: In our study of 7 cases of condylar fractures at various levels and different kind of displacement and deviation were treated by ORIF by using 5 different approaches. Highcondylar fractures and intra capsular fractures can be approached through pre-auricular incision, endaural incision,modified Blair incision. Subcondylar fractureand ramus fracture can be approached through retromandibular, modified retromandibular and Modified blair incision.